The absolut present of word: Interview with Eduardo Coutinho (In memorian) - Leandro, Anita (2024)
Twenty years ago, Eduardo Coutinho (1933-2014) was interviewed by researcher, teacher, and filmmaker Anita Leandro and by anthropologist and filmmaker Marc-Henri Piault, after shooting Peões (Metalworkers, 2004). Initially published in French, in 2005, with the title Le présent absolu de la parole. Sur Eduardo Coutinho, in the FAL MAG magazine (Revue France Amérique Latine), the interview – now being published in Portuguese for the first time – brings several reflections on Coutinho's documentary practice and on the making of Peões.